b - Baesens, Bart; e uthor; Broucke, Seppe vanden, 1986- (Indianapolis, IN : John Wiley & Sons, Inc., 2015)
A comprehensive Java guide, with samples, exercises, case studies, and step-by-step instruction. Beginning Java Programming: The Object Oriented Approach is a straightforward resource for getting started with one of the world's most enduringly popular programming languages. Based on classes taught by the authors, the book starts with the basics and gradually builds into more advanced concepts. The approach utilizes an integrated development environment that allows readers to immediately apply what they learn, and includes step-by-step instruction with plenty of sample programs. Each chapter contains exercises based on real-world business and educational scenarios, and the final chapter uses case studies to combine several concepts and put readers' new skills to the test. Beginning Java Programming: The Object Oriented Approach provides both the information and the tools beginners need to develop Java skills, from the general concepts of object-oriented programming. Learn to: understand the Java language and object-oriented concept implementation; use Java to access and manipulate external data; make applications accessible to users with GUIs; [and,] streamline workflow with object-oriented patterns. The book is geared for those who want to use Java in an applied environment while learning at the same time. Useful as either a course text or a stand-alone self-study program, Beginning Java Programming is a thorough, comprehensive guide.
A general introduction to programming -- Getting to know Java -- Setting up your development environment -- Moving toward object-oriented programming -- Controlling the flow of your program -- Handling exceptions and debugging -- Delving further into object-oriented concepts -- Handling input and output -- Working with databases in Java -- Accessing web sources -- Designing graphical interfaces -- Using object-oriented patterns.
"Wrox programmer to programmer."
Produced by the publisher.
Held by CAPER-BC, Langara College.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on October 21, 2021).
John Wiley and Sons
Keywords: Java (Computer program language); Java (Langage de programmation); BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Java (Computer program language); handbooks; manuals (instructional materials); Handbooks and manuals; Handbooks and manuals; Guides et manuels